2018
DOI: 10.2478/pjct-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

A novel DOPO-g-KH550 modification wood fibers and its effects on the properties of composite phenolic foams

Abstract: A novel 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) graft γ-amino propyl triethoxy silane (KH550) was synthesized and introduced on the surface of wood fi ber. Finally DOPO-g-KH550 treated wood fi ber (DKTWF) was used to prepare DKTWF composite phenolic foams (DKTWFCPF). The structures of DOPO-g-KH550 was acknowledged by Fourier transform infrared (FT-IR) and nuclear magnetic resonance ( 1 H-NMR). The structures of DKTWF were confi rmed by FT-IR. Compared with wood fi ber, the diffraction peaks'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…They observed that the addition of only 0.5 wt% of glass fibres (L = 6.4 mm, D = 10 µm) improved the flexural strength by 35%. Modified wood fibres improved also the flexural strength [85].…”
Section: Additive Route: Fibres and Particles Reinforcementmentioning
confidence: 91%
See 2 more Smart Citations
“…They observed that the addition of only 0.5 wt% of glass fibres (L = 6.4 mm, D = 10 µm) improved the flexural strength by 35%. Modified wood fibres improved also the flexural strength [85].…”
Section: Additive Route: Fibres and Particles Reinforcementmentioning
confidence: 91%
“…While the compressive strength increased by about 52% after adding 6 wt% of non-modified aramid fibres, the improvement of 67% was obtained for modified aramid fibres in the same amount, which supported the efficiency of the surface modification. In opposition, Ma et al [85] have reported a that the addition of 4 wt% modified wood fibres decreased the compressive strength by 36%.…”
Section: Additive Route: Fibre Reinforcementmentioning
confidence: 95%
See 1 more Smart Citation
“…4. For DOPO, the signal around 6.56 to 8.86 ppm was corresponded to the phenyl protons [28][29][30][31]. For CNSL, the chemical shifts of H a , H b , H c , H d and H e were observed at 0.97 ppm, 1.38 ppm, 2.10 ppm, 1.64 ppm and 2.60 ppm respectively, and the signal around 5.44 ppm (H f ) was corresponded to double bonds protons [10].…”
Section: H Nmr Of Dopo-g-cnslmentioning
confidence: 99%